Biosynthesis of Nio Nanoparticles Using Prodigiosin Pigment and its Evaluate of Antibacterial Activity Against Biofilm Producing MDR- Pseudomonas Aeruginosa - Yaaqoob, L. A.; Younis, R. W.; Kamona, Z. K.; Altaee, M. F.; Abed, R. M. (Iraqi Journal of Science, 2023)
The entire investigation’s focus was on the production of nickel oxide nanoparticles (NiONPs), using prodigiosin pigments produced by Serratia marcescens as a stabilizing and reducing agent. Nickel oxide nanoparticles are synthesized using nickel sulfate NiSO4 (10mg) with a concentration of prodigiosin (10g/100ml). Biosynthesized NiO nanoparticles have been characterized by using many techniques, such as (UV-Vis, AFM, XRD, FTIR, and FE-SEM). The AFM analysis revealed that NiONPs have an average diameter size of (41.77 mm), and the FE-SEM Image displays Spherical. Additionally, the effect of NiONPs with different concentrations on the bacteria Pseudomonas aeruginosa was measured and the inhibition zone reached to (29 mm). Biosynthesis of NiONPs using prodigiosin was shown to have promising activity as an antibacterial against the biofilm-producing Pseudomonas aeruginosa.